EFFECTIVENESS OF THE GUIDED DISCOVERY MODEL BASED VIRTUAL LAB PhET TOWARD MASTERY STUDENTS’ CONCEPT ON TOPIC PHOTOELECTRIC EFFECT - Habibbulloh, Muhammad (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2019)
Research has been conducted to determine the effectiveness of the guided discovery model based on the virtual lab PhET (Physics Education technology) on mastering students' concepts in the photoelectric effect material. The purpose of this study is describing the feasibility of learning, student activity, and the effectiveness of the model applied to the mastery of student concepts. This type of research is quantitative descriptive with the design of one group pretest-posttest. The data obtained were in the form of learning accuracy questionnaires, student activities, and the results of the pretest and posttest mastery of students' concepts. Analysis of data on implementation and activities of students used percentage of agreement, while mastery of students' concepts was analyzed descriptively quantitatively through homogeneity, normality, and N-gain test. Based on data and analysis, it was concluded that the implementation of categorical learning was very good, student activities were in good category, and guided discovery models based on virtual labs PhET were effectively used to improve mastery of students' concepts in the photoelectric effect material.